Spin Effects in Laser-Assisted Semirelativistic Excitation of Atomic Hydrogen by Electronic Impact (Journal of Atomic and Molecular Sciences, 2021)
New insights into our understanding of the semirelativistic excitation of atomic hydrogen by electronic impact have been made possible by combining the use of polarized electron beams and intense laser field. The paper reviews relativistic theoretical treatment in laser-assisted electron scattering with particular emphasis upon spin effects. Different spin configurations for inelastic electron-atom collisions is also discussed. The role of laser field in such collision is of major importance and reveals new information on the dynamics of the collision process. The examined modern theoretical investigations of such relativistic laser-assisted collisions have shown that the need for experimental data is of a paramount importance in order to assess the accuracy of our calculations.
Keywords: spin effects; laser assisted; QED calculation.